REVIEW POLITICAL ORDER AND POLITICAL DECAY: FROM THE INDUSTRIAL REVOLUTION TO THE GLOBALIZATION OF DEMOCRACY (Journal of the Spanish Institute for Strategic Studies, 2018)
Yoshihiro Francis Fukuyama, North American author, of Japanese origin, wasborn in Chicago in 1952. As a Political Scientist, he has a wide repertoire inthe field of international politics and development, although he obtained hismost important international recognition as a writer in 1992 with the publication ofThe End of History and the Last Man, which has been translated into 23 languages.He studied at Cornell, Yale, and Harvard Universities, and keeps in contact with theacademic world teaching at Stanford University. Of neo-conservative ideas, he has hadan active role in the politics of the United States during the terms of office of the lastthree presidents, particularly as a member of the Project for the New American Century,in support of the United States world leadership. Presently, he is acknowledgedas one of the great thinkers of our days.